The Impact of Migration on Achieving Sustainable Development Goals (SDGs)@Viksit Bharat 2047 - Mallayya (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
Migration, both internal and international, is a defining feature of globalization and human mobility in the 21st century. While migration provides economic, social, and cultural benefits, it also creates challenges for sustainable development. Recognizing its importance, the 2030 Agenda for Sustainable Development integrates migration within several goals, most notably SDG 10.7 (facilitating safe, regular, and responsible migration). This paper examines the relationship between migration and the SDGs, analyzing its opportunities, risks, and long-term implications for development. It further highlights policy recommendations to maximize the positive contributions of migration while minimizing adverse effects.